Pendidikan Sejarah dalam Kurikulum di Republik Federal Jerman - Kurniawati Kurniawati (Program Studi Pendidikan Sejarah Pascasarjana UNJ, 2015)
The aim of this article is to find out what philosophy behind the education curriculum in Germany,its system and structure especially on history curriculum to be compared with Indonesiaâ€s experience.Traditionally the German educational system is strongly influenced by the tradition of naturalistichumanism - specifically those of the Humbold philosophy regarding as Bildung. History Education is acompulsory subject that is given to students from grade 6-10 as much as two hours of lessons per week,while in grade 10-12 or 13 lessons, history is no longer a compulsory subject. In grade 6-9 curriculum isbased on chronological history revolves around the history of Western Civilization, in grade 10 historylessons relating to contemporary history in the 20th century, while in grade 11-12 / 13 history lessonfocused on the history of modern Europe and non- European history.